2003
DOI: 10.1253/circj.67.401
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Coronary Artery Disease by Multislice Spiral Computed Tomography Using a New Retrospectively ECG-Gated Image Reconstruction Techniqu-Comparison With Angiographic Results-

Abstract: The present study was designed to investigate the accuracy of multislice spiral computed tomography (MSCT) in detecting coronary artery disease, compared with coronary angiography (CAG), using a new retrospectively ECG-gated reconstruction method that reduced cardiac motion artifact. The study group comprised 54 consecutive patients undergoing MSCT and CAG. MSCT was performed using a SOMATOM Volume Zoom (4-detector-row, Siemens, Germany) with slice thickness 1.0 mm, pitch 1.5 (table feed: 1.5 mm per rotation) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 14 publications
1
62
0
Order By: Relevance
“…9 With the development of MSCT, however, it has become possible to visualize the precise anatomy of the moving heart. [10][11][12] Moreover, the recently introduced 16-slice MSCT system, which allows simultaneous acquisition of 16 submillimeter slices, enables more detailed imaging, not only of stenosed coronary arteries but also of stents implanted within coronary arteries. 13 Our aim, therefore, was to evaluate the usefulness of 16-slice MSCT for clinical evaluation of the patency of metallic stents within coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…9 With the development of MSCT, however, it has become possible to visualize the precise anatomy of the moving heart. [10][11][12] Moreover, the recently introduced 16-slice MSCT system, which allows simultaneous acquisition of 16 submillimeter slices, enables more detailed imaging, not only of stenosed coronary arteries but also of stents implanted within coronary arteries. 13 Our aim, therefore, was to evaluate the usefulness of 16-slice MSCT for clinical evaluation of the patency of metallic stents within coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The CVS has also been used for radiofrequency catheter ablation, 4 mapping, 5 and defibrillation. 6,7 Visualization of the CVS has been attempted by angiography, 8,9 echocardiography 10,11 and electron-beam computed tomography (CT), 12,13 and recently contrast-enhanced multidetector row spiral computed tomography (MDCT) has been used to noninvasively visualize coronary artery stenosis by creating high-quality 3-dimensional (3-D) images, [14][15][16][17][18][19] However, there has not been a study to date that has attempted to analyze the CVS using MDCT, so the aim of the present study was to investigate the applicability and image quality of contrast-enhanced visualization of the CVS by MDCT using retrospective ECG gating. Attention was also focused on the presence and number of coronary veins on the lateral aspect of the left ventricle (LV), which are the optimal sites for placing pacing leads for LV pacing in patients with advanced heart failure.…”
mentioning
confidence: 99%
“…They reported that the image reconstruction phase determined by Method P could consistently avoid the atrial contraction period in each cardiac cycle and could provide much better image quality than the method in which the beginning of the image reconstruction phase was positioned at the midpoint between the RR intervals of the cardiac cycle. 19,20 As previously described, the point at which the reduced ejection period changes into the isovolemic relaxation period is supposed to be near the end point of the T wave. The ventricular movement is expected to be larger at the beginning of the rapid filling period than at the end of the contraction period.…”
Section: Discussionmentioning
confidence: 99%